FETAL ULTRASOUND ANATOMY AND MORPHOMETRIC PARAMETERS OF THE ULNA AND RADIUS IN FETUSES OF 19-22 WEEKS OF GESTATION - О. Коваль; Т. Хмара; І. Заморський; А. Ходан; М. Кривчанська (Неонатологія, хірургія та перинатальна медицина)
Assessment of the length of the long tubular bones of the fetus, including the ulna and radius, is used in modern fetal anatomy and to estimate the gestational age of the fetus. In addition, assessment of the length of the long tubular bones of the skeleton is important for the detection of skeletal disproportion, namely achondroplasia and hypochondroplasia. Congenital defects can also be diagnosed prenatally by ultrasound. Objective of the research. To determine the morphometric parameters of ulna and radius length at 19-22 weeks of gestation. Materials and methods. To determine the fetal anatomy of the structures of the ulna and radius, we used an imaging method such as ultrasound scanning. Fetometric measurements of the length of the fetal ulna and radius were performed using intravital ultrasound (IVUS) at 19-22 weeks of gestation. We analyzed 44 fetal ultrasounds in women with normal pregnancies. Results. From the 19th to the 22nd week of intrauterine development, the length of the right ulna increases from 2.77±0.17 mm to 3.22±0.12 mm, while the length of the left ulna increases from 2.73±0.16 mm to 3.26±0.15 mm. From the 19th to the 22nd week of intrauterine development, the length of the right radius increases from 2.50±0.12 mm to 2.92±0.22 mm, while the length of the left radius increases from 2.46±0.12 mm to 2.88±0.20 mm. Conclusions. Fetometry of the ulna and radius bones by ultrasound is one of the basic studies of fetal development. The bones of the forearm grow almost equally during the study period and no signifi cant diff erences in their growth are observed. We found that the period of intensive growth of forearm bones in the second trimester is 20-21 weeks of gestation, and the period of slow growth is 19-20 weeks of gestation.